The Evolving Dynamics of Afghanistan–Pakistan Relations: Implications of the Taliban’s Resurgence Post-2021 - Abdul Wasi Popalzay (Chinese Journal of International Review)
This study critically examines the evolving dynamics of Afghanistan–Pakistan relations following the Taliban’s resurgence in 2021, a development that has intensified security, diplomatic, and economic challenges within South Asia. Historically defined by conflict, proxy warfare, and intermittent cooperation, the relationship between Afghanistan and Pakistan is now further complicated by the Taliban’s governance and the resurgence of the Tehrik-i-Taliban Pakistan (TTP). By applying a regional security complex framework, this research investigates how security threats, cross-border tensions, and geopolitical alignments shape current interactions between the two countries. Through qualitative analysis, this study identifies key factors influencing these dynamics, such as Pakistan’s internal security policies and public sentiment, Afghanistan’s fragmented governance structure, and the strategic roles of regional powers like China, India, Russia, and Iran. Findings indicate that cross-border attacks by the TTP, unresolved territorial disputes, and fluctuating diplomatic engagements are pivotal to understanding the ongoing instability. Economic dependencies and infrastructure projects, although potential avenues for cooperation, remain secondary to pressing security concerns. This study emphasizes the implications of Afghanistan–Pakistan relations for broader regional stability, particularly for counterterrorism efforts and humanitarian issues linked to refugee flows and human rights under Taliban rule. Ultimately, the research highlights the urgent need for effective diplomatic mechanisms, regional partnerships, and consistent international engagement to foster stability in South Asia. By assessing these complex dimensions, the study provides critical insights into the prospects and policy directions required to navigate Afghanistan–Pakistan relations in an increasingly volatile context.